Antibiotik Empirik di Intensive Care Unit (ICU) - Aditya, Ricky; Kestriani, Nurita Dian; Maskoen, Tinni T. (Majalah Anestesia dan Critical Care, 2016)
Penemuan jenis antibiotik baru diimbangi dengan penemuan resistensi dari bakteri tersebut terhadap beberapa obat.Secara garis besar, antibiotik dibagi menjadi tiga golongan berdasarkan cara kerja, spektrum, dan efek bakterisidal.Terapi antibiotik terhadap pasien kritis merupakan hal yang menjadi perhatian di dunia akibat tingginya mortalitasdan morbiditas. Aspek efektifitas terapi terus menjadi perhatian akibat peningkatan kebutuhan ruang Intensive CareUnit. Kontrol infeksi dan pemilihan antibiotik yang sesuai merupakan intervensi utama dan harus menjadi prioritasdalam manajemen pasien kritis. Pengetahuan mengenai farmakokinetik dan farmakodinamik antibiotik merupakanfaktor yang esensial karena penentuan dosis antibiotik berkaitan dengan keluaran pasien kritis. Perubahan padavolume of distribution dan clearance antibiotik pada pasien kritis mungkin berefek pada target konsentrasi obatdalam serum. Hal ini menjadi bukti bahwa parameter pharmacokinetics (PK)/pharmacodynamics (PD) berperanterhadap efek obat yang terkait dengan keluaran pasien dan resistensi. Kata kunci: Antibiotik, farmako dinamik, farmako kinetik, ICU, pasien kritis The discovery of new types of antibiotic resistance offset by the discovery of bacteria to multiple drugs. In general,antibiotics are divided into three groups based on the spectrum shape, and the bactericidal effect. Antibiotictherapy for critically ill patients is a concern in the world due to the high mortality and morbidity. Aspects of theeffectiveness of therapy remains a concern due to the increasing needs of the ICU. Pemilihian infection controland appropriate antibiotic is a major intervention and should be a priority in the management of patients in criticalcondition. Knowledge of the pharmacokinetics (PK) and pharmacodynamics (PD) of antibiotics is essential todetermine the doses of antibiotics related to production factor of critically ill patients. Changes in the volumeof distribution and clearance of antibiotics in critically ill patients may have an effect on a target serum drugconcentrations. This is proof that the PK/PD parameter contribute to the effects associated with the drug and theoutput resistance of the patient. Key words: Antibiotic, Critical patients, ICU, pharmacodynamis, pharmacokinetis Reference Davies, JD. Origins and Evolution of Antibiotic Resistance. Microbiology and Molecular Biology Reviews, 2010;74(3): 417–33. Waksman, SA. What is an Antibiotic or an Antibiotic Substance?. Mycoglia. 1947; 39(5):565–9. Bruton, LL., Chabner AB., & Knollmann CB. Goodman and Gilman’s The Pharmacological Basis of Therapeutics, 12th ed. California: McGraw-Hill Education, 2010. Aminov, RI. A Brief History of the Antibiotic Era: Lessons Learned and Challenges for the Future. Frontier in Microbiology. 2010;1(134). Davies, J. & Davies D. Origins and Evolution of Antibiotic Resistance. Microbiology and Molecular Biology Review.2010;74(3). Saga, T. & Yamaguchi, K. History of Antimicrobial Agents and Resistant. Research and Reviews.2009;52(2). Kohanski MA, Dwyer DJ, Collins JJ. How Antibiotics Kill Bacteria: from Target to Network. Microbiology.2010;8(1). Mitchigan State University. Antimicrobial Resistence Learnig Site Pharmacology. 2011, Diakses pada 28 Oktober 2015 dari: http://amrls.cvm.msu.edu . Roberts, JA. & Jeffrey L. Pharmacokinetic Issues for Antibiotics in the Critically Ill Patient. Continuing Medical Education Article: Concise Definite Review. 2009;37(3):540–51. McKellar, QA., SF. Sanchez Bruni, & DG. Jones. Pharmacokinetic/Pharmacodynamic Relationship of Antimicrobial Drugs Used in Veterinary Medicine. Journal of Veterinary Pharmacology and Therapeutics. 2004;27:503–14. Finberg, RW. & Guharoy R. Clinical Use of Anti-infective Agents: A Guide on How to Prescribe Drugs Used to Treat Infections. Springer Science & Business Media, LLC. 2012. p. 5–13 Maramba-Lazarte, CC. Determining Correct Dosing Regimens of Antibiotics Based on the Their Bacterial Activity. Pediatric Infectious Disease Society of the Philippines Journal, 2010;11(2):44–9. Levison, ME. & Levison JH. Pharmacokinetics and Pharmacodynamics of Antibacterial Agent. Infectious Desease Clinical North America, 2009;24(3):791–830. Bennet, PN. Brown, MJ. Clinical Phamacology, 9th ed. Spain: Elvisier, 2003.